ANALYSIS OF OPTIMAL PORTFOLIO PERFORMANCE USING MARKOWITZ MODEL AND SINGLE INDEX MODEL (CASE STUDY ON LQ45 INDICES) - Salsa Aldila; Noor Prio Sasongko (Universitas Mercu Buana, 2022)
This study aims to analyze performance of Markowitz Model and Single Index Model to construct optimal portfolio. Descriptive analysis method with quantitative approach is used in this study. Construction of optimal portfolio using historical daily data from the first semester of the study and evaluation of optimal portfolio performance using historical daily data form the second semester of the study. This study assumed that investment applied as the optimal portfolio constructed by both models. Therefore, performance evaluation both portfolios conducted on second semester of the study using Sharpe ratio, Treynor ratio, and Jensen’s Alpha. This study shows that there are no significance differences of optimal portfolio performance using Markowitz Model and Single Index Model.